Endodontic Reintervention on Tooth with Apicalis Periodontitis: A case report - nugroho, juni jekti; Basir, Irawati (Hasanuddin University, 2022)
Objective: This case report evaluated endodontic reintervention on posterior tooth with failed treatment.Case: A 22-year-old female patient came to RSGMP complained the upper right posterior tooth that was painful when chewing. The tooth was diagnosed previously treated teeth.Results: Endodontic reintervention procedure was initially by removing the gutta-percha, determination of working length, root canal preparation using the crown down pressureless technique. Root canal obturation was performed using single cone technique and post endodontic restoration using a PFM crown. After treatment the patient had no subjective complaints and gingiva was normal. Conclusion: Endodontic reintervention is an effective method for tooth that have failed treatment.